Potential of Malaysian local honey as an antibacterial agent - Ainul Hafiza , A.H.; Yusof, N.; Maimon, A. (Universiti Kebangsaan Malaysia, 2005)
A laboratory study was carried out to study the microbiological quality of local honey and its potential as an antibacterial agent. Five local honeys namely, Belimbing, Gelam (Sample 1,2, and 3), Durian (Sample 1 and 2), Kelapa and Tualang were studied. Microbial colony count of each sample was determined using filtration method. Screening for antibacterial action against Staphylococcus aureus was carried out using agar diffusion method. The result showed that all samples had low colony counts ranging from 37 cfu/ml in Kelapa honey to 161 cfu/ml in Durian honey (Sample 2). All samples showed a very clear zone of inhibition for bacterial growth and there was significant difference (ANOVA, p<0.05) among the samples. Belimbing honey showed the biggest diameter (2.1cm) and Gelam honey – Sample 3 had the smallest (1.7 cm).